1996
DOI: 10.1074/jbc.271.36.22218
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-associated Protein Is a Folding Chaperone for Low Density Lipoprotein Receptor-related Protein

Abstract: The 39-kDa receptor-associated protein (RAP) is a receptor antagonist that inhibits ligand interactions with the receptors that belong to the low density lipoprotein receptor gene family. Our previous studies have demonstrated that RAP interacts with the low density lipoprotein receptor-related protein (LRP) within the endoplasmic reticulum and prevents premature interaction of ligands with the receptor. To analyze whether RAP is also involved in the folding of LRP during receptor biosynthesis, we generated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
173
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(177 citation statements)
references
References 30 publications
4
173
0
Order By: Relevance
“…LRP is a member of the low-density lipoprotein receptor gene family of endocytic receptors (26)(27)(28). The 39-kDa RAP can be used as a ligand (23). Internalization of cell-surface bound recombinant RAP is rapid and after dissociation from the receptor in the endosomes, it is transported to the lysosome whereas the LRP recycles back to the plasma membrane (29).…”
Section: Internalization Of the Lrp4ghr (245-434) Chimer Is Independementioning
confidence: 99%
“…LRP is a member of the low-density lipoprotein receptor gene family of endocytic receptors (26)(27)(28). The 39-kDa RAP can be used as a ligand (23). Internalization of cell-surface bound recombinant RAP is rapid and after dissociation from the receptor in the endosomes, it is transported to the lysosome whereas the LRP recycles back to the plasma membrane (29).…”
Section: Internalization Of the Lrp4ghr (245-434) Chimer Is Independementioning
confidence: 99%
“…Indeed, an alternative model for the regulation of ligand binding by RAP proposes a RAP-induced conformational change in the LRP molecule (9,18,39). It was demonstrated that both LRP and RAP harbor multiple interaction sites for their mutual interaction (7,8,13). Based on analysis of the primary structure, it was revealed that RAP contains an internal triplication of structural autonomous domains comprising residues 1-100 (D1), 101-200 (D2), and 201-323 (D3) (13,40).…”
Section: Kinetics Of Ligand Binding To Lrp Cluster II and Cluster Imentioning
confidence: 99%
“…Evidence is accumulating that the clusters of LDLRA domains constitute the ligand binding domains of the receptor (6 -10). Except for receptor-associated protein (RAP) binding to clusters III and IV (1,7,8), only cluster II was shown to be involved in ligand binding (6 -10). Specifically, it has been demonstrated that ␣ 2 -macroglobulin-light chain, complexes between urokinase-type plasminogen activator (u-PA) and its inhibitor plasminogen activator inhibitor-1 (PAI-1), lactoferrin, an anti-LRP Fab fragment (denoted Fab A8), and RAP bind to cluster II.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether identical structural arrangements are present within the LBR of other members of the LDL receptor gene family remains to be elucidated but appears to be highly likely due to their sequence homology and functional similarities. Studies with LRP and its minireceptors indicate that intramolecular disulfide bond formation is of crucial importance for the proper folding and trafficking of the receptor within the early secretory pathway (12)(13)(14). Within the endoplasmic reticulum (ER), a 39-kDa receptor-associated protein (RAP) associates with LRP upon receptor synthesis and assists the folding and trafficking of the receptor (12).…”
mentioning
confidence: 99%